Workplace Stress: Issues and Management - Ida Miharti (Universitas Negeri Gorontalo, 2020)
This paper tries to show that workplace stress should be managed. Workplace stress can be influences individual life, not only in its family but also in its society. Work and nonwork factor can be interacting each other, that can be made stress become. So, it is important to find how to manage individual stress, especially in workplace stress.